Study of symptoms of anxiety and depression and quality of life before and after radioactive iodine intake in patients with thyroid cancer - Banihashem, Shahab; Arabzadeh, Mehdi; Ghotbi, Mohsen (Researcher Bulletin of Medical Sciences, 2020)
Introduction: Thyroid cancer can affect the quality of life of patients and no validated study has been conducted to evaluate the quality of life in patients with thyroid cancer in Iran. The purpose of this study was to evaluate the changes of quality of life in patients with thyroid cancer treated with radioactive iodine. Materials and Methods: According to a prospective longitudinal study, quality of life and mood in these patients were studied by two questionnaires: Short Form Health Survey (SF36) and Hospital Anxiety and Depression Scale (HADS) provided to the patients by the researcher. The questionnaires were completed one month before iodine injection, on the day of injection, at the end of the second week, and sixth month after radioactive iodine injection. The patients were treated in two groups of 100 and 150 μ Curie. After completing the questionnaires, the resulting scores at four different time points were evaluated and compared. Results: The mean SF36 scores were lower than one month before iodine intake and after 6 months, the mean scores were lower than one month before iodine intake. The mean HADS scores one month after iodine intake were not significantly different from the time of iodine intake, but after two weeks, anxiety and depression were reduced, and the result continued till the sixth months. No difference was found in the levels of anxiety and depression between the doses of 100 and 150 μ Curie. Conclusion: The highest level of anxiety and depression and quality of life during the first two weeks of iodine intake reduced with time and iodine intake dose did not affect it.